PELAYANAN, SUKU BUNGA, KECEPATAN PROSES TERHADAPKEPUTUSAN KONSUMEN MENGAMBIL KREDIT MELALUI MINATKONSUMEN: Analisis Pengaruh Faktor Pelayanan, Tingkat Suku Bunga, dan Kecepatan Proses terhadap Keputusan Konsumen dalam Mengambil Kredit dengan Variabel Mediasi Minat Konsumen - Adriana Loppo (Jurnal Akub Effata, 2016)
The purpose of this study was to determine and to analysis 1) influence on consumerservicesto the consumer's interest to apply for credit 2) The effect of the interest rate on the interest of the consumer to apply for credit to apply for credit 3) The effect of speed on the interest of the consumer to apply for credit 4) Effect of service the consumer decision-making to decide credits 5) the effect of interest rates on consumer decisionmaking to decide credits 6) the effect of speed on the consumer's decision process to decide on taking loans 7) the influence of consumer interest in the consumer decisionmaking to determine the credit The study found that 1) Effect of variable service to the consumer interest has standardized estimate (regression weight) of 0.522, with CR (Critical Ratio = identical to the value of t-test) of 3.110 at 0.012 probability. CR value 3.110> 2.000 and 0.012 probability <0.05 indicates that the effect of variable services to consumer interest is significant. 2) The effect of variable interest rates on consumer interest has standardized estimate (regression weight) of 0.906, with CR (Critical Ratio = identical to the value of t-test) of 10.851 on the probability *** (><0.001). Value CR 10.851>2.000 and probability *** <0.05 indicates that the effect of variable interest rates on consumer interest is significant. 3) Effect of variable speed of the process towards the consumer interest has standardized estimate (regression weight) of 0.850, with CR (Critical Ratio = identical to the value of t-test) of 9.115 on the probability *** (><0.001). CR value 9.115>2.000 and the probability *** <0.05 indicates that the influence of the variable speed of the process is a significant consumer interest. 4) Effect of variable service to the consumer decision hasstandardized estimate (regression weight) of 0.638, with CR (Critical Ratio = identical to the value of t-test) of 8.625 on the probability *** (><0.001). CR value 8.625>2.000 and the probability ***